2016
DOI: 10.1016/j.ijedudev.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Schooling children with disabilities: Parental perceptions and experiences

Abstract: A B S T R A C TSchooling of children with disabilities has become an important development agenda, as also emphasized in the SDGs. This paper examines how parents of children with disabilities from low income families living in a rural community in India understand and experience the schooling of their child with disabilities. Data were collected through semi-structured interviews with mothers. Findings suggest that mothers greatly valued schooling both for its short and long term benefits; however they were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Research in Delhi private schools concluded that teachers were making minor modifications to respond to the needs of children with disabilities, without undertaking any significant changes to their classroom practices (Jha, 2010). Similar observations were captured in Singal's (2016) study in government rural schools in Karnataka, and Taneja Johansson's (2015) research in private urban schools in West Bengal. Both studies noted that while there was no negativity towards children with disabilities, teachers made few largely insignificant efforts to accommodate them, all of which lacked any substantial engagement with learning.…”
Section: Small Changes But Not Enoughsupporting
confidence: 80%
See 1 more Smart Citation
“…Research in Delhi private schools concluded that teachers were making minor modifications to respond to the needs of children with disabilities, without undertaking any significant changes to their classroom practices (Jha, 2010). Similar observations were captured in Singal's (2016) study in government rural schools in Karnataka, and Taneja Johansson's (2015) research in private urban schools in West Bengal. Both studies noted that while there was no negativity towards children with disabilities, teachers made few largely insignificant efforts to accommodate them, all of which lacked any substantial engagement with learning.…”
Section: Small Changes But Not Enoughsupporting
confidence: 80%
“…Schooling as leading to a better future, has transformed the thinking of parents in relation to their child(ren) with disabilities, as seen among the families in rural Karnataka (Singal, 2016). In another study, young adults with disabilities who had attended school in rural Dewas, focused on social and personal gains, such as being respected in their community and increased self-confidence, when asked to reflect on the outcomes of schooling (Singal, Jeffery, Jain, & Sood, 2009).…”
Section: Small Changes But Not Enoughmentioning
confidence: 99%
“…Firstly, our research highlights the need to recognise the value that parents appear to place on the schooling of their children with disabilities, an issue that has been raised in previous research in India (Singal 2016b), for example, but is often overlooked by policymakers. Specifically, in our sample, some children are enrolled in private schools.…”
Section: Discussionmentioning
confidence: 92%
“…As "providers" for children, they look ahead with a deep concern for the future. A majority of families worry whether school education would be of "value in real life" and question its quality too (Singal, 2016). Parents bringing up children with moderate to severe disabilities anticipate unemployment.…”
Section: Introductionmentioning
confidence: 99%